Productivity, supervision and morale in an office situation - Katz, Daniel; Maccoby, Nathan; Morse, Nancy C. (Ann Arbor, Mich. : Institute for Social Research, University of Michigan, 1950)
This study was the initial project in a long range research program in human relations in group organization being carried on by the Survey Research Center of the University of Michigan. The subjects were clerical workers and their supervisors.
Includes bibliographical references.
hza 13/07/2018
Loans
Keywords: Personnel management; Office management